PERENCANAAN SISTEM PENYALIRAN TAMBANG, STUDI KASUS : PIT TIMUR BUKIT WRANGLER PT. ANTAM TBK. UNIT BISNIS PERTAMBANGAN NIKEL SULAWESI TENGGARA - Aulia Mutiara Chakti; Rusli HAR (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. Based on the data analysis of rainfall at 2010-1019, obtained a rainfall plan is 30,105 m/day with different rain intensiti in each catchmen area with a return period of 25 years. The location of the reasearch is Pit Bukit Wrangler PT. Antam, in 2020 it has 2 catchmen areas with different areas, the area for the catchmen area in area 1 is 0.052959 km² and 0.1186071 km² in area II. Total discharge is 0.3390 m/second in catchmen area I and 0.4803 m²/second in catchmen area II, while the volume of groundwater that enters the Pit Bukit Wrangler is 0.122 m/second. The are 2 open channels which have different dimensions. The open channel I has a wet cross-sectional area of 1.411 m, a wet circumference is 3.149, a hydraulic radius is 0.448 m, and a slope of a channel is 2.228 m. While in open channel II it has a wet cross-sectional area is 1.819 m, a wet circumference is 3.58 m, the hydraulic radius is 0.508 m, and the slope of the channel is 1.039 m. At the Pit Bukit Wrangler there is only one sump and there is one Kubota NS-100 pump unit, but after calculating the current total pump head, the total head currently exceeds actual pump head total. The total head of the pump work and to avoid overflow of water that is in the sump to the floor of the mining pit, and additional 6 pump units have been made. The Pit Bukit Wrangler has one main settling pond with different capacities for each compartment. The settling pond volume at Bukit Wrangler is 2,588.116 m and the total volume deposited solids is 3,864.11 m³/day, and the time required for dredging activities is about 669.78 days or 21 month in one dredging.Key Word : Rainfall, Catchmen Area, Pump, Sump, Sediment Pond